Evaluasi Penerapan Gmp Dan Ssop Pada Industri Rumah Tangga Pengolahan Amplang Ikan Di Singkawang - Harnatasya; Farisy, Salman Al; Hidayat, Riki; Ulya, Novia; Wulan, Putri; Merdekawati, Dewi (Jurnal Perikanan dan Kelautan, 2025)
This study aims to evaluate the implementation of Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP) in a home-scale amplang (fish cracker) processing industry using Spanish mackerel in Singkawang City. The method used was direct observation of production facilities, processing activities, and supporting infrastructure, assessed against the standards of Ministry Regulation No. 17 of 2019 and No. 75/M-IND/PER/7/2010. The results indicated compliance in areas such as space separation, clean water usage, and production recordkeeping. However, weaknesses were identified in employee training, hygiene supervision, sanitation documentation, and waste management. In conclusion, GMP and SSOP principles have been applied but not yet optimally, requiring continuous improvements in human resources, facilities, and documentation systems.